(untitled) (African Journal of Biomedical Research, 2024)
The emergence and reemergence antibacterial resistance has made it more difficult for a choice of effective antibiotics to treat infections caused by bacteria. Antimicrobial resistant bacteria are usually spread from person to person, or from non-human sources in the environment. These non-human sources could aid in the spread of resistant genes as well as resistant pathogens. A systematic review was carried out in accordance to PRISMA guidelines, 55 relevant literatures were included from the 152 searched were identified from PubMed, Google Scholar and AJOL using related specific search terms. Only studies carried out or related to Nigeria from January, 2000 to August, 2022 were considered eligible. All data obtained from the reviewed articles were presented in percentages using MS Excel 2013. The most prevalent antibacterial genes were blaCTX-M-15 and blaTEM with the prevalence of 2.77%; sul1 and tetA with the prevalence rate of 2.31%; tetM with the prevalence rate of 2.08%; and blaCTX-M, blaSHV, mecA, sul2 and tetB having a prevalence of 1.85%. The sources from which these resistance genes were identified are humans (55.7%) and non-humans (44.3%). The most prevalent bacteria harboring these resistant genes were Escherichia coli (13.2%), Staphylococcus aureus (5.66%) and Klebsiella pneumoniae (5.03%). A Antibiotics resistance has continued to threaten the success of modern medicine, with more resistance strains emerging constantly. The wide distribution of antibacterial resistance genes in non-human sources makes them reservoirs of these resistant genes which could potentially be transferred from commensal microorganisms to human pathogens